The information supply by the Peruvian media during election periods and their role in strengthening democracy: a case analysis - Vílchez Samanez, Prisea Georgina (2023)
This article analyzes the characteristics of the information supplied by the Peruvian print media in a specific election period, the 2018 regional and municipal election, and reflects on their role and contribution to democracy. For data collection, media monitoring, a quantitative technique that uses a codebook and coding sheet as instruments, was employed. A total of 3261 news items from six selected newspapers (three from Lima and three from other regions) were reviewed. This research has shown some trends or patterns of the information supplied by the selected media in the 2018 election, including the fact that the focus of the electoral process was the candidate and not the citizen; there was limited visibility of key issues, such as citizen participation in the electoral process or political party funding; most of the news about the elections was “framed” as a conflict; the news article was the most used journalistic format; and little opinion was expressed, which prevented from having broader and better debates, as well as public deliberation on issues of common interest. In addition, the study brought to light the characteristics of the information supply that question the political role of the six analyzed media and their contribution to the strengthening of democracy.